Double jeopardy: COVID-19, coup d'état and poverty in Myanmar - Boughton, Duncan; Headey, Derek D.; Mahrt, Kristi; Cho, Ame; Diao, Xinshen; Lambrecht, Isabel B.; Minten, Bart; Goeb, Joseph; Masias, Ian; Belton, Ben; Aung, Nilar; San, Cho Cho (Wiley, 2023)
Myanmar experienced multiple COVID shocks as well as a military takeover in February 2021. Impacts on household poverty remain uncertain, however, because large-scale in-person surveys were impossible during the pandemic and heightened internal conflict. We use ex ante simulation models and phone survey evidence to estimate the poverty effects of these shocks and identify factors correlated with them. While each approach has limitations, and cannot explicitly validate each other, they both indicate rising rural and urban poverty and capital-depleting coping mechanisms. Wider use of simulation modeling could help mobilize social protection faster than waiting for survey results in emergencies.